2021
DOI: 10.25299/sportarea.2021.vol6(3).6612
|View full text |Cite
|
Sign up to set email alerts
|

The application of discord as an effort to increase students’ wellbeing in physical education learning during the COVID-19 emergency

Abstract: Physical education learning in high school during the current Covid-19 emergency, teachers have difficulty delivering material, controlling, evaluating, and providing learning feedback, especially on basic competencies that contain motion. The research objective was to improve students’ wellbeing in high school physical education learning during the Covid-19 emergency by implementing the disdcord application. Students’ wellbeing in this study, the researcher described three indicators of achievement, that is: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…Previous research demonstrated that Discord is an effective and free application converted for learning [24]. Additionally, it is utilized in lessons that positively impact student abilities, suitability, and satisfaction with the learning process [40]. The user experience findings confirm that mobile learning with the application can foster creativity in students and encourage lecturers to adopt more approaches in their teaching.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Previous research demonstrated that Discord is an effective and free application converted for learning [24]. Additionally, it is utilized in lessons that positively impact student abilities, suitability, and satisfaction with the learning process [40]. The user experience findings confirm that mobile learning with the application can foster creativity in students and encourage lecturers to adopt more approaches in their teaching.…”
Section: Discussionmentioning
confidence: 54%
“…Discord has been adapted for educational purposes and has proven to be an efficient and free application [24]. It has been used in sport lessons and positively impacted students' ability, suitability, and satisfaction with their learning experiences [40].…”
Section: Discord Application For Learningmentioning
confidence: 99%
“…Likewise, this Discord platform has been efficient in the area of physical education, as indicated by scholars Mashud et al (2021), who point out that it has been implemented in educational environments related to sports classes, generating a positive impact on skills, aptitudes and level. of student satisfaction with respect to their learning experiences.…”
Section: General Comparative Results Of the Entry And Exit Questionna...mentioning
confidence: 99%
“…Tugas guru diantaranya adalah menciptakan suasana atau iklim belajar mengajar yang dapat memotivasi peserta didik untuk senantiasa belajar dengan baik dan bersemangat. Dengan kondisi belajar yang menantang dan berkompetisi secara sehat yang mendorong peserta didik untuk belajar, akan berdampak positif dalam pencapaian prestasi hasil belajar secara optimal (Mashud et al 2021).…”
Section: Pendahuluanunclassified